Use of Oral Vancomycin for Clostridioides difficile Infection and the Risk of Vancomycin-Resistant Enterococci. (3rd September 2019) - Stevens, Vanessa W; Khader, Karim; Echevarria, Kelly; Nelson, Richard E; Zhang, Yue; Jones, Makoto; Timbrook, Tristan T; Samore, Matthew H; Rubin, Michael A
Abstract: Background: Vancomycin is now a preferred treatment for all cases of Clostridioides difficile infection (CDI), regardless of disease severity. Concerns remain that a large-scale shift to oral vancomycin may increase selection pressure for vancomycin-resistant Enterococci (VRE). We evaluated the risk of VRE following oral vancomycin or metronidazole treatment among patients with CDI. Methods: We conducted a retrospective cohort study of patients with CDI in the US Department of Veterans Affairs health system between 1 January 2006 and 31 December 2016. Patients were included if they were treated with metronidazole or oral vancomycin and had no history of VRE in the previous year. Missing data were handled by multiple imputation of 50 datasets. Patients treated with oral vancomycin were compared to those treated with metronidazole after balancing on patient characteristics using propensity score matching in each imputed dataset. Patients were followed for VRE isolated from a clinical culture within 3 months. Results: Patients treated with oral vancomycin were no more likely to develop VRE within 3 months than metronidazole-treated patients (adjusted relative risk, 0.96; 95% confidence interval [CI], .77 to 1.20), equating to an absolute risk difference of −0.11% (95% CI, −.68% to .47%). Similar results were observed at 6 months. Conclusions: Our results suggest that oral vancomycin and metronidazole are equally likely to impact patients' risk of VRE. In the setting of stable CDI incidence, replacement of metronidazole with oral vancomycin is unlikely to be a significant driver of increased risk of VRE at the patient level. In this multicenter, retrospective cohort study of patients with Clostridioides difficile infection, the use of oral vancomycin did not increase the risk of vancomycin-resistant Enterococci infection at 3 or 6 months compared to metronidazole.